2012
DOI: 10.3390/ijerph9072537
|View full text |Cite
|
Sign up to set email alerts
|

Commensal Pseudomonas Species Isolated from Wastewater and Freshwater Milieus in the Eastern Cape Province, South Africa, as Reservoir of Antibiotic Resistant Determinants

Abstract: Pseudomonas species are opportunistic pathogens with implications in a wide range of diseases including cystic fibrosis and sickle cell anaemia. Because of their status as multidrug resistant (MDR) and extremely drug resistant (XDR) bacteria Pseudomonas species represent a threat to public health. Prevalence, antibiogram and associated antibiotic resistant genes of Pseudomonas species isolated from freshwater and mixed liquor environments in the Eastern Cape Province of South Africa were assessed. Polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 29 publications
3
25
1
Order By: Relevance
“…Likewise, in agreement with our ndings, a study carried out in Ma keng in the North West Province of South Africa, isolated P. aeruginosa and other Pseudomonas species from both drinking and surface waters [37]. However, contrary to our ndings, a study carried out in Alice, Eastern Cape, South Africa on wastewater samples found a lower occurrence rate of 11.1% [38]. This disparity is most likely due to different treatment processes used in water puri cation, or it can be assumed that WWTP does not totally eliminate bacteria especially MDR strains since these organisms are resilient to the treatment processes and eventually play a role in the transmission and spread of antimicrobial resistance.…”
Section: Isolation and Antimicrobial Susceptibility Testingsupporting
confidence: 89%
“…Likewise, in agreement with our ndings, a study carried out in Ma keng in the North West Province of South Africa, isolated P. aeruginosa and other Pseudomonas species from both drinking and surface waters [37]. However, contrary to our ndings, a study carried out in Alice, Eastern Cape, South Africa on wastewater samples found a lower occurrence rate of 11.1% [38]. This disparity is most likely due to different treatment processes used in water puri cation, or it can be assumed that WWTP does not totally eliminate bacteria especially MDR strains since these organisms are resilient to the treatment processes and eventually play a role in the transmission and spread of antimicrobial resistance.…”
Section: Isolation and Antimicrobial Susceptibility Testingsupporting
confidence: 89%
“…fluorescens groups [ 12 ]. Representatives from these groups have been isolated from a variety of habitats such as: soils and rhizospheres [ 13 15 ], drains[ 14 ], fresh and salt water [ 16 20 ], plants [ 21 , 22 ], and in clinical settings [ 23 25 ]. Nevertheless, despite substantial overlap in the environments from which they have been isolated, they differ in the resources they are able to use [ 26 , 27 ], in their temperature tolerances [ 26 , 28 ], and they have been found to differ in their relative abundances in some types of environments.…”
Section: Introductionmentioning
confidence: 99%
“…putida group strains to be more common than P . fluorescens group strains in household sites [ 14 ]; Igbinosa et al [ 20 ] found more P . putida than P .…”
Section: Introductionmentioning
confidence: 99%
“…2. Igbinosa et al [24] reported that all isolates (100%) from fresh water and mixed liquor samples from Alice were susceptible to ciprofloxacin and gentamicin. Conversely, all (100%) were resistant to penicillin.…”
Section: Antibiotic Resistance Patterns Of the Isolated Pseudomonasmentioning
confidence: 99%